The handbook of manufacturing engineering. planning and instructional methods - Crowson, Richard (Handbook of manufacturing engineering., 2006)
Volume two of the second edition of the comprehensive Handbook of Manufacturing Engineering illuminates the role of the manufacturing engineer as the key component of factory operation. The focus is on the planning and instruction duties that are critical to successful operations management, which fall upon the manufacturing engineer who may be unfamiliar with many of the planning and costing aspects. The book provides detailed descriptions of successful methods, including statistical methods for component reliability, practical cost estimating, and control of production and materials. The edi.